Pengaruh Green Human Resources Management dan Green Innovation terhadap Business Sustainability - Tri Suyantiningsih; Nur Wening (Jurnal Rimba Riset Ilmu manajemen Bisnis dan Akuntansi, 2025)
This study aims to analyze the influence of Green Human Resources Management and Green Innovation on Business Sustainability. The Green Human Resources Management approach includes recruitment, training, performance appraisal, and compensation practices oriented towards environmental conservation. Meanwhile, green innovation focuses on the development of environmentally friendly products, processes, and business models. The sampling technique used is purposive sampling with a total of 100 respondents. Data collection was carried out using an online questionnaire after testing validity and reliability. The analysis in this study employs SEM-PLS. The results indicate that Green Human Resources Management does not have an effect on Business Sustainability. In contrast, Green Innovation has a significant positive effect on Business Sustainability. The implementation of enhanced green innovation has been proven to increase operational efficiency and strengthen the company's image as an environmentally conscious business. This study emphasizes the importance of integrating human resource management and environmentally friendly innovation to achieve better business sustainability